Redox-Controlled Site-Specific α2‒6-Sialylation - Lu, Na (J Am Chem Soc, 2019)
The first bacterial α2−6-sialyltransferase cloned from Photobacterium damselae (Pd2,6ST) has been widely applied for the synthesis of various α2−6-linked sialosides. However, the extreme substrate flexibility of Pd2,6ST makes it unsuitable for site-specific α2−6-sialylation of complex substrates containing multiple galactose and/or N-acetylgalactosamine units. To tackle this problem, a general redox-controlled site-specific sialylation strategy using Pd2,6ST is described. This approach features site-specific enzymatic oxidation of galactose units to mask the unwanted sialylation sites and precisely controlling the site-specific α2−6-sialylation at intact galactose or N-acetylgalactosamine units.